PERAN ORIENTASI PASAR MEMEDIASI PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA UKM INDUSTRI KERAJINAN ENDEK - Pramesti, Ni Made Vera; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen, 2016)
The purpose of this study is to determine the effect of entrepreneurial orientation on market orientation, market orientation on SMEs performance, entrepreneurial orientation on SMEs performance, and mediating effect of market orientation at endek weaving Small and Medium Enterprises (SMEs) in Klungkung. Study population is 37 endek weaving SMEs and sampling technique is census method. Data collected by questionnaires and interviews. Path analysis and sobel was used to test the hypotheses. Analysis result shows that three hypotheses is accepted. Entrepreneurial orientation has significant and positive effect on market orientation, market orientation has significant and positif effect on business performance, entrepreneurial orientation has significant and positive effect on business performance, and effect entrepreneurial orientation on business performance is mediated by market orientation endek weaving SMEs in klungkung.
Keywords: entrepreneurial orientation, market orientation, SMEs performance